Governance, information flow, and stock returns - Dumitrescu, Ariadna; Zakriya, Mohammed (Journal of Corporate Finance, 2022)
We analyze the evolution of governance-returns relationship in the last three decades and show that poor governance stocks outperform good governance ones after 2008. Previously, good governance stocks outperformed poor governance ones before this relationship disappeared in 2001. The novel reversal and reappearance of the relationship in 2008 can be explained by sophisticated investors learning to recognize governance risks and becoming more prudent after the global financial crisis. Our results show that investors could have identified via price and risk channels that the poorly governed firms face higher uncertainty regarding their future earnings power after 2008. Furthermore, following the crisis, we observe that institutional investors update their governance preferences through information-induced learning.